Investigating the Impact of Ethno-Physics Learning on Students’ Critical Thinking Skills - Alibar, Muhamad; Prayogi, Saiful; Habibi, Habibi (Universitas Pendidikan Mandalika, 2024)
This study examines the impact of Ethno-Physics Learning on enhancing students’ critical thinking skills by integrating indigenous cultural knowledge into the physics curriculum. Traditional physics instruction, which often relies on rote memorization and passive learning, has been found insufficient in developing the analytical and problem-solving abilities necessary for both academic achievement and real-world applications. In contrast, Ethno-Physics Learning contextualizes abstract scientific concepts within culturally relevant frameworks, thereby fostering active inquiry and deeper cognitive engagement. Utilizing a quasi-experimental design with non-equivalent control groups, the research involved Grade 10 students from two classes. The experimental group received instruction on the topic of Work and Energy through Ethno-Physics Learning methods, while the control group experienced conventional lecture-based teaching. Both groups underwent pretesting and posttesting to assess their critical thinking skills across various dimensions, including analysis, inference, evaluation, explanation, and decision-making. Statistical analyses, incorporating tests for normality and homogeneity followed by paired samples t-tests, revealed that although improvements were noted in both groups, the experimental group exhibited significantly greater gains in critical thinking abilities. These findings suggest that integrating local ethnoscience into physics education not only makes scientific theories more accessible and meaningful but also cultivates the higher-order cognitive skills essential for effective problem-solving. The study highlights the transformative potential of Ethno-Physics Learning and recommends its incorporation into science curricula to enhance student engagement and learning outcomes in diverse educational settings.